Morocco : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that Morocco's macroeconomic conditions have improved since 2012, but growth has remained sluggish. In 2016, growth slowed owing to a sharp contraction in agricultural output and subdued nonagricultural activity. The unemployment rate decreased to 9.6 percent in the third quarter of 2016 while youth unemployment remains high at 21.8 percent. Morocco's medium-term prospects are favorable, with growth expected to rebound to 4.4 percent in 2017 and reach 4.5 percent by 2021. However, risks remain substantial, and relate mainly to growth in advanced and emerging market economies, geopolitical tensions in the region, world energy prices, and global financial market volatility.